Characterisation of clinical response and transcriptional profiling of proliferating CD8 T cells in the blood of cancer patients after PD-1 monotherapy or combination therapy - Peng Li; Haydn Kissick; Rebecca C Obeng; Tahseen H Nasti; Christiane S Eberhardt; Rafi Ahmed; Zhengjia Chen; Warren J Leonard; Suresh S Ramalingam; Andreas Wieland; Annapaola Mariniello; Jeffrey M Switchenko; et al. (BMJ Oncology)
Objective Immune checkpoint inhibitors (ICI) that block the programmed cell death 1 (PD-1) pathway have shown promise with limited benefit. We and others have shown in small patient cohorts that an early proliferative CD8 T-cell response in the blood may be predictive of clinical response. However, these studies lack detailed analyses and comparisons between monotherapy and combination therapies.Methods and analysis We analysed longitudinal blood samples from 103 patients with cancer who received αPD-1 monotherapy or combined with anti-cytotoxic T lymphocyte-associated protein 4 (αCTLA-4) or chemotherapy. Transcriptional analysis of CD8 T cells after the first treatment cycle with effector cells generated following yellow fever virus (YFV-17D) vaccine-induced infection was also compared.Results An early proliferative (Ki-67+) CD8 T-cell response was observed after cycle 1 in 60 patients (58.3%). Patients with early-and-sustained proliferative responses (cycle 1 and beyond) had better clinical responses and survival than patients with an early-but-limited response (p=0.02). The proliferating cells had an effector-like phenotype. The transcriptional profiles of the effector-like CD8 T cells were similar irrespective of treatment type or clinical response but distinct from that of YFV-specific effector CD8 T cells.Conclusions Our data suggest that early proliferative CD8 T-cell response in the blood is predictive, and that an early-and-sustained proliferative response may further identify patients with prolonged survival. The ICI-induced effector-like CD8 T cells are transcriptionally distinct from highly functional YFV-specific cells, suggesting opportunities for improved T-cell effector function with combination therapies for better clinical outcome.